Efficacy of biochar application on seed germination and early growth of forest tree species in semi-evergreen, moist deciduous forest. Issue 3 (2nd July 2020) - Gogoi, Lina; Gogoi, Nirmali; Borkotoki, Bikram; Kataki, Rupam
ABSTRACT: The effect of forest litter biochar on seed germination and early growth of two tree species ( Trewia nudiflora and Lagerstroemia speciosa ) was examined in a selected forest area of Nameri National Park, India. All tested biochar applications (from 1 t ha −1  to 6 t ha −1 ) significantly increased germination percentage, germination index, vigor index, and dry weight of 30 days old seedlings for both species, compared to the control (no biochar). The highest increases were obtained for both species and for all the above variables when biochar was added at the highest rate (6 t ha −1 ). Results of the seedling growth experiment, with the same biochar applications (from 1 t ha −1  to 6 t ha −1 ), show that 2 years after planting, all biochar doses had a significant depressing effect on the growth of the two species, except for the highest dose (6 t ha −1 ) which shows a low but significant increase in growth for both species.